DECISION SUPPORT SYSTEM USING AHP METHOD FOR TEACHER PERFORMANCE ASSESSMENT - Rahmawati, Rahmawati; Wulandari, Dewi Ayu Nur (Jurnal Pilar Nusa Mandiri, 2020)
One effort to measure the level of quality in schools is by measuring the performance aspects of teachers as professional educators who teach at the school. The teacher performance aspect is measured as one of the promotion requirements for a higher position or as a recommendation condition in order to take part in teacher certification activities. In order for teacher performance appraisal to be carried out objectively, a method is needed to assist in the teacher performance appraisal process. AHP method can be used to assist in decision making. This is because the AHP method is a model for structured and comprehensive decision making. From the calculation using the AHP method, it was found that the first priority was obtained by Indra with a weight of 0, 7317 or 73.17%, the second priority was obtained by Reni with a weight value of 0.2279 or 22.79% and the lowest priority was obtained by Supriyatna with a weight value 0.0604 or 6.04%.